Rancang Bangun Alat Pengukur Kalori Makanan Pintar Berbasis Smartphone Android - Sudaryono, Tri, Ratnasari N R, S.T.,M.T (2017)
The research's purpose is to design and create the Scale measurement tool that is used for calculating the amount of calories of any foods. It is designed as the nutrient expert to maintain of human health and also able to understand the needed nutrient intake of our body. The measurement process is controlled by Android Smartphone. The measurement is using the load cell as the weight sensor and the pixy camera CMUcam5 as the food menu detector. The result of load cell and pixy camera CMUcam 5 are managed and operated by arduino. the data that is obtained from the measurement will be transmitted to the android smartphone via bluetooth HC-05. everyfood menu has different calories. 219 gr for Rice has 383 cals, 48,9 gr of an egg has 7,9 cals, and 99,8 gr for kale has 28 cals then the total calories for these three menu are 490 cals. The measurement result will determine whether the needed calories of once meal-time is apropriate or less or even over. when the needed calories is less, it will make the body becoming thinness and malnutrition. when it is excess then it will make the body becoming obesity. Keywords: Arduino, bluetooth HC-05, camera pixy CMUcam5, load cell, kalori, smartphone android.